Efektivitas Model Numbered Head Together dengan Pendekatan Joyful Learning Berbantuan Wordwall Terhadap Hasil Belajar - Moch. Nizam Nuruzzaman; Agus Prasetyo Kurniawan; Ni'matus Sa'diyah (Jurnal Inovasi Pendidikan Matematika (JIPM), 2025)
This study aims to determine the effectiveness of the cooperative learning model Numbered Heads Together (NHT) with a Joyful Learning approach assisted by Wordwall media in improving students’ mathematics learning outcomes at grade VII of MTs Negeri 1 Lamongan. This research employed a quantitative method with a pre-experimental design using a one-group pretest-posttest model. The sample consisted of 24 students from class VII-I selected through purposive sampling. The research instrument was a mathematics achievement test administered before and after the treatment. Data was analyzed using normality test, Paired Sample t-Test, and N-Gain calculation. The results indicated a significant improvement in students’ learning outcomes, as shown by the t-test significance value of 0.001 (<0.05) and an N-Gain score of 0.7855 categorized as high. These findings demonstrate that the application of the NHT model with Joyful Learning assisted by Wordwall media is effective in enhancing students’ learning outcomes. The implication suggests that combining NHT, joyful classroom atmosphere, and interactive digital media can serve as an innovative alternative strategy in mathematics learning.